MANAJEMEN PENGEMBANGAN DOSEN SEBAGAI UPAYA MENINGKATKAN MUTU SEKOLAH TINGGI PARIWISATA AMPTA YOGYAKARTA - Lestari, Siti Rokhmi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2014)
The aim of this study is to describe the planning and development of lecturers human resources in AMPTA Tourism School as well as to know the profesionalism of lecturers and quality assurance in the AMPTA Tourism School of Yogyakarta. From this study it can be concluded that, in general, human resource planning and development of lecturers as well as quality assurance in AMPTA Tourism School have not been fully implemented in accordance with the existing regulations and legislation. However, AMPTA Tourism School is on the right track in terms of lecturers profesionalism development and networking establisment with external stakeholders. Implementation of human resources development is carried out through formal and informal ways. Keywords: Management, Human Resources, Development, Lecturer, Quality, Tourism School.